Vagal Blocking Improves Glycemic Control and Elevated Blood Pressure in Obese Subjects with Type 2 Diabetes Mellitus - S. Shikora; J. Toouli; M. F. Herrera; B. Kulseng; H. Zulewski; R. Brancatisano; L. Kow; J. P. Pantoja; G. Johnsen; A. Brancatisano; K. S. Tweden; M. B. Knudson; et al. (Journal of Obesity)
Background. An active device that downregulates abdominal vagal signalling has resulted in significant weight loss in feasibility studies. Objective. To prospectively evaluate the effect of intermittent vagal blocking (VBLOC) on weight loss, glycemic control, and blood pressure (BP) in obese subjects with DM2. Methods. Twenty-eight subjects were implanted with a VBLOC device (Maestro Rechargeable System) at 5 centers in an open-label study. Effects on weight loss, HbA1c, fasting blood glucose, and BP were evaluated at 1 week to 12 months. Results. 26 subjects (17 females/9 males, 51±2 years, BMI 37±1 kg/m2, mean ± SEM) completed 12 months followup. One serious adverse event (pain at implant site) was easily resolved. At 1 week and 12 months, mean excess weight loss percentages (% EWL) were 9±1% and 25±4% (P<0.0001), and HbA1c declined by 0.3±0.1% and 1.0±0.2% (P=0.02, baseline 7.8±0.2%). In DM2 subjects with elevated BP (n=15), mean arterial pressure reduced by 7±3 mmHg and 8±3 mmHg (P=0.04, baseline 100 ± 2 mmHg) at 1 week and 12 months. All subjects MAP decreased by 3 ± 2 mmHg (baseline 95 ± 2 mmHg) at 12 months. Conclusions. VBLOC was safe in obese DM2 subjects and associated with meaningful weight loss, early and sustained improvements in HbA1c, and reductions in BP in hypertensive DM2 subjects. This trial is registered with ClinicalTrials.gov NCT00555958.